PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Puji Tri Lestari; Elok Sudibyo; Ernita Vika Aulia (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This research aimed to determine the effect of TGT learning model on improvement students’ cognitive learning outcomes in the human digestive system material and students’ responses to the TGT model. This research used a one group pretest posttest design. The data collection techniques used were test method to measure students’ learning outcomes, questionnaire method to determine students’ responses and observation method to measure learning implementation. The results of this research showed that there was an effect of TGT model on improvement students’ learning outcomes marked by the N-Gain score in high category. The implementation of the TGT model obtained responses from stundents with a very positive category and the learning implementation of the TGT model was in the very good category. The conclusion of this research was that the TGT learning model had an effect to improve students’ cognitive learning outcomes in the human digestive system material.